Plant diseases and their management - Chattopadhyay, S.B.; Mustafee, Tulipada (Jaipur, Raj. : Pointer Publishers : Distributed by Aavishkar Publishers' Distributors, 2008)
Contibuted articles.
Includes bibliographical references and index.
Keywords: Plant diseases; Plant diseases -- India